Optical characterization of solution prepared Cu2SnS3 for photovoltaic applications. Issue 1771 (2015) - de Wild, Jessica; Robert, Erika V. C.; El Adib, Brahime; Dale, Phillip J.
ABSTRACT: Monoclinic Cu2 SnS3 was made by solution based processing of the precursor metals after which the samples are annealed in a sulphur environment. XRD and Raman spectra shows that the monoclinic phase was synthesised. One sample was further etched in KCN and HCl to remove possible secondary phases. Transmission spectra show that the material has two optical transitions and in conjunction with reflection data absorption spectra were calculated. The two optical transitions are determined to be 0.91 and 0.98 for the unetched sample and 0.90 and 0.95 eV for the etched sample. The values of the optical transitions are within the error the same and thus etching does not affect the values of these optical transitions. Photoluminescence spectra map show only one luminescence peak with a maximum at 0.95 eV, which is consistent with the values found by absorption spectra. This in combination with the Raman spectra and XRD indicates that the sample contains only one polymorph of Cu2 SnS3, which is monoclinic. Therefore the two optical transitions are intrinsic to monoclinic Cu2 SnS3 .